The small subunit of DNA polymerase D (DP1) associates with GINS–GAN complex of the thermophilic archaea in Thermococcus sp. 4557. Issue 9 (8th May 2019) - Lu, Shuhong; Zhang, Xuesong; Chen, Kaiying; Chen, Zimeng; Li, Yixiang; Qi, Zhongquan; Shen, Yulong; Li, Zhuo
Abstract: The eukaryotic GINS, Cdc45, and minichromosome maintenance proteins form an essential complex that moves with the DNA replication fork. The GINS protein complex has also been reported to associate with DNA polymerase. In archaea, the third domain of life, DNA polymerase D (PolD) is essential for DNA replication, and the genes encoding PolDs exist only in the genomes of archaea. The archaeal GAN (G INS‐a ssociated n uclease) is believed to be a homolog of the eukaryotic Cdc45. In this study, we found that the Thermococcus sp. 4557 DP1 (small subunit of PolD) interacted with GINS15 in vitro, and the 3′–5′ exonuclease activity of DP1 was inhibited by GINS15. We also demonstrated that the GAN, GINS15, and DP1 proteins interact to form a complex adapting a GAN–GINS15–DP1 order. The results of this study imply that the complex constitutes a core of the DNA replisome in archaea. Abstract : In Thermococcus sp. 4557, the small subunit of DNA polymerase D (DP1) interacted with GINS15 in vitro, and the 3′–5′ exonuclease activity of DP1 was inhibited by GINS15. We also demonstrated that the GAN, GINS15, and DP1 proteins interact to form a complex adapting a GAN–GINS15–DP1 order. The results of this study imply that the complex constitutes a core of the DNA replisome in archaea.